Sistem Hukum Adat dan Implementasinya - Diah Anggraeni Novitasari (Universitas Palangka Raya, 2024)
Customary law is a law that applies to a particular custom in which the customary law itself has been hereditary and has been in collaboration with customary law in other regions. Customary law has two different characteristic forms, the first is written customary law and unwritten customary law. Customary law in force and that has been implemented by the community of customary owners themselves mostly use customary law that is not written and has been outlined by their ancestors for problem solving or finding a solution to a case using customary law in force in their respective customs. Therefore, researchers are interested in studying the customary law system and its implementation in a community group. By using previous research methods that are then developed by the author.